Stream sediments as a contamination repository around an abandoned uranium mine, central Portugal - Carvalho, Paula (2021)
In central Portugal, some abandoned uranium mines were already remediated [1]. However, some others may be responsible for potential environmental risks due to geochemical dynamics. The abandoned Barrôco D. Frango uranium mine has an open pit lake 50 m long and 10 m wide, and a ~40,020 m3 mine dump. A contamination assessment was carried out along the main stream, by collecting water samples in four seasons (2016 - 2017) and stream sediments (2016). Surface waters are generally near-neutral to alkaline (5.83 - 7.55), with uranium, thorium and arsenic concentration ranges of 4.5 - 37.3 µg/L, 2.7 -11.0 µg/L and 4.8 - 39.5 µg/L, respectively. Water´s uranium concentrations tend to be higher in winter due to the dissolution of uranium minerals in dumps, while any distinction is observed with thorium. Water has arsenic and heavy metals lower than the permitted values for agricultural irrigation. However, sediments with median uranium concentration of 53.3 mg/kg (41.9 - 189 mg/kg) and thorium of 49.0 mg/kg (27.2 - 81.9 mg/kg), present moderate to considerable ecological risk (RI= 34.31 - 78.79), mainly due to arsenic concentrations (25.4 - 60.6 mg/kg).